2015
DOI: 10.3382/ps/pev251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental zinc source and level on antioxidant ability and fat metabolism-related enzymes of broilers

Abstract: The objective of the present study was to investigate the effects of dietary supplemental Zinc (Zn) source and level on antioxidant ability and fat metabolism-related enzymes of broilers. Dietary treatments included the Zn-unsupplemented corn-soybean meal basal diet (control) and basal diets supplemented with 60, 120, or 180 mg Zn/kg as Zn sulfate, Zn amino acid chelate with a weak chelation strength of 6.5 quotient of formation (Qf) (11.93% Zn) (Zn-AA W), Zn proteinate with a moderate chelation strength of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 27 publications
3
35
0
3
Order By: Relevance
“…In accordance with the present findings, Liu et al. () found that dietary supplementation of Zn at 60 mg/kg in the corn–soy diet improved Cu‐Zn‐SOD in the breast and thigh muscles ( p < .05) and liver ( p < .01) of chickens. Zinc is important for the function and structure of Cu‐Zn‐SOD, which comprised more than 90% of SOD and protects the body from free radical and oxidative stress (Noor, Mittal, & Iqbal, ; Wang et al., ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with the present findings, Liu et al. () found that dietary supplementation of Zn at 60 mg/kg in the corn–soy diet improved Cu‐Zn‐SOD in the breast and thigh muscles ( p < .05) and liver ( p < .01) of chickens. Zinc is important for the function and structure of Cu‐Zn‐SOD, which comprised more than 90% of SOD and protects the body from free radical and oxidative stress (Noor, Mittal, & Iqbal, ; Wang et al., ).…”
Section: Resultssupporting
confidence: 92%
“…In agreement with these results, serum Zn level was positively correlated with Zn level in the diet (Darlen & Arlette, ). Dietary supplementation of Zn improved Zn status by increasing the content of Zn in the breast, liver and thigh muscles of chickens (Liu et al., ). Contradicting results were obtained by Bartlett and Smith () who found that there was no significant effect of dietary Zn levels on plasma Zn concentration in chickens exposed to heat stress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data are in harmony with those reported by Ahmadi et al (2014) who indicated that nano zinc supplementation decreased MDA concentration compared to control. Also, Liu et al (2015) stated that supplemental zinc decreased malondialdehyde (MDA) level in the liver. We could speculate that dietary Zn might strengthen the oxidative defenses and decrease the MDA content of muscles, which would contribute to higher quality and longer shelf life of meat.…”
Section: 6antioxidant Enzyme Activitymentioning
confidence: 99%
“…Likewise, there was considerable digestion and absorption of minerals with a nutritional organic source of trace minerals (zinc, copper, manganese, iron, calcium, and phosphorus) compared to an inorganic source in pigs [34]. To our knowledge, there have been several reports that showed varied responses of animals supplemented with Zn and Cu from different sources [1][2][3]35,36], but the triazine hydrazone complexes had not been investigated yet. Our findings, therefore, could contribute a new potential organic complex of trace minerals that would facilitate the research of the growth-promoting products and develop some novel pharmacological drugs.…”
Section: Discussionmentioning
confidence: 99%